-3+8(w+3)=-11

Simple and best practice solution for -3+8(w+3)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+8(w+3)=-11 equation:


Simplifying
-3 + 8(w + 3) = -11

Reorder the terms:
-3 + 8(3 + w) = -11
-3 + (3 * 8 + w * 8) = -11
-3 + (24 + 8w) = -11

Combine like terms: -3 + 24 = 21
21 + 8w = -11

Solving
21 + 8w = -11

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 8w = -11 + -21

Combine like terms: 21 + -21 = 0
0 + 8w = -11 + -21
8w = -11 + -21

Combine like terms: -11 + -21 = -32
8w = -32

Divide each side by '8'.
w = -4

Simplifying
w = -4

See similar equations:

| 4=-9(f+1) | | -2t=4y | | 10-6(2+x)=4 | | 10a+-35=8a+1 | | R=P+PTR | | 4(f-2)=24 | | 3x+24=22 | | 3-h=2 | | A=P+PTR | | Mx+Ny=y | | =3e^2*8e^5 | | 10(s-9)=-198 | | x+6t+5= | | 3(x+11)=7x+5 | | 6(2-3n)=6n | | 6c-20=40 | | x^2-2(n-3)x+4n=0 | | 1.6-d=12.8 | | -9=5(y-6)-8y | | 10-2q=5+0.5q | | -3(2x-6)=-6x-18 | | =9a^6*a^9 | | 5(8x-2)=-130 | | 1. 2x-34=-20 | | 2x-27=x+13 | | -4x+6(x+3)=6 | | 21yd=ft | | (4b-5)*(2b+7)= | | 2(20+x)=5x+4 | | 3(r+2)=6r-5 | | x+(x-48)+3(x-48)=898 | | -19=-3v+7(v-5) |

Equations solver categories